2022
DOI: 10.3390/life12081115
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Lycium Ruthenicum Murr Anthocyanins in Cr (VI)-Induced Mitophagy in DF-1 Cells

Abstract: Cr (VI) is an extremely toxic environment and professional pollutant that seriously damages mitochondrial dysfunction when it enters a cell. Anthocyanins possess anti-oxidant, antiaging, and antifatigue properties. The regulatory effect of Lycium ruthenicum Murr anthocyanin (LRMA) on Cr (VI)-induced mitophagy in DF-1 cells was determined. The experimental design was divided into blank group, groups subjected to Cr (VI) and Cr (VI), and LRMA co-treatment groups. Cell viability was determined by the CCK-8 assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Tomato anthocyanin ameliorates Cr(VI)-induced autophagy by inhibiting ER stress (Liu et al, 2020). Lycium ruthenicum Murr anthocyanin can inhibit autophagic activity and reduce mitochondrial damage through downregulation of the PINK1/Parkin pathway, resulting in a protective effect on DF-1 cells (Guo et al, 2022), Platycodon grandiflorus polysaccharides could improve Cr(VI)-induced mitochondrial autophagy by inhibiting ROS and restoring MMP (Hao et al, 2020). These studies could serve as bases for the treatment of Cr poisoning.…”
Section: Detoxifying Substancesmentioning
confidence: 95%
“…Tomato anthocyanin ameliorates Cr(VI)-induced autophagy by inhibiting ER stress (Liu et al, 2020). Lycium ruthenicum Murr anthocyanin can inhibit autophagic activity and reduce mitochondrial damage through downregulation of the PINK1/Parkin pathway, resulting in a protective effect on DF-1 cells (Guo et al, 2022), Platycodon grandiflorus polysaccharides could improve Cr(VI)-induced mitochondrial autophagy by inhibiting ROS and restoring MMP (Hao et al, 2020). These studies could serve as bases for the treatment of Cr poisoning.…”
Section: Detoxifying Substancesmentioning
confidence: 95%
“…Li L. et al [71] investigated the mechanism of LRM anthocyanins in treating gouty arthritis, identifying potential targets and pathways through tissue lipidomics, cyberpharmacology, and molecular docking. Guo S. et al [72] demonstrated that LRM anthocyanins mitigate mitochondrial damage and autophagy induced by chromium (VI) in cells, suggesting protective effects against heavy metal toxicity.…”
Section: Other Bioactivitiesmentioning
confidence: 99%
“…Similarly, Lycium Ruthenicum Murr anthocyanins (LRMA) have also been shown to inhibit autophagy and mitophagy in DF‐1 cells that were administrated with Cr (VI). These effects could be attributed to the fact that LRMA reduced oxidative stress and inhibited the putative protein kinase 1 (PINK1)/Parkin pathway (Guo et al., 2022). Accordingly, Wistar rats were applied to demonstrate that anthocyanins mitigated the adverse effects of Cr (VI) on the adrenal gland.…”
Section: Influence Of Anthocyanins On Food Contaminants From the Natu...mentioning
confidence: 99%